Modelling the Growth Inhibition Kinetics of Rhodotorula sp. strain MBH23 (KCTC 11960BP) on Acrylamide (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
The yeast Rhodotorula sp. Strain MBH23 (KCTC 11960BP) is an efficient acrylamide-degrader and is able to tolerate high concentrations of acrylamide. A primary modelling exercise for the growth of this yeast on acrylamide yields important specific growth rates which were utilized successfully for secondary modelling exercise which gave Luong as the best model. The Luongâ€™s constants; maximal growth rate, half-saturation constant for maximal growth, maximal concentration of substrate tolerated and curve parameter that defines the steepness of the growth rate decline from the maximum rate symbolized by ïmax, Ks, Sm, and n (Â± standard error) were 0.099Â±0.017 hr-1, 17.34 Â± 5.0 mg/L, 2053.0 Â±56.0 mg/L and 0.801Â±0.202, respectively. The Luong model indicates that acrylamide is toxic and inhibits the growth of this yeast. To date, this is the first time that such a modelling exercise was utilized to model growth kinetics on acrylamide.
Keywords: Rhodotorula sp.; Acrylamide-degrading; modified Gompertz; Haldane; Modelling